Addressing Special Educational Needs and Disability in the Curriculum: Maths - Wallace, Max (London : Taylor and Francis, 2017)
"The SEND Code of Practice (2015) reinforced the requirement that all teachers must meet the needs of all learners. This topical book provides practical, tried and tested strategies and resources that will support teachers in making maths lessons accessible and interesting for all pupils, including those with special needs. The author draws on a wealth of experience to share his understanding of special educational needs and disabilities and show how the maths teacher can reduce or remove any barriers to learning. Offering strategies that are specific to the context of maths teaching, this book will enable teachers to:adopt a 'problem solving' approach to ensure students use and apply mathematics at all times during their learningdevelop students' understanding of mathematical ideasstructure lessons to empower and actively engage students create a mutually supportive classroom which maximises learning opportunitiesplan the classroom layout and display to enhance learning, such as displaying number lines, vocabulary lists and pupils' worksuccessfully train and fully use the support of their teaching assistants.An invaluable tool for continuing professional development, this text will be essential for secondary maths teachers (and their teaching assistants) seeking guidance specific to teaching maths to all pupils, regardless of their individual needs. This book will also be of interest to secondary SENCOs, senior management teams and ITT providers. In addition to free online resources, a range of appendices provide maths teachers with a variety of pro forma and activity sheets to support effective teaching. This is an essential tool for maths teachers and teaching assistants, and will help to deliver successful, inclusive lessons for all pupils."--Provided by publisher.
chapter 1 Meeting special educational needs and disabilities: Your responsibility -- chapter 2 The inclusive mathematics classroom -- chapter 3 Teaching and learning -- chapter 4 Monitoring and assessment -- chapter 5 Managing support and intervention -- chapter 6 Real pupils in real classrooms.
Keywords: Mathematics -- Study and teaching; Special education; Great Britain; Children with disabilities -- Education; Inclusion and Special Educational Needs; Mathematics; SENCOs; EDUCATION / Special Education / General; EDUCATION / Teaching Methods & Materials / Mathematics